Investigating the Influence of the Solar activity on the Electron Density of Mars's Ionospheric Layer - R. Al-Ubaidi, Najat M.; A. Jabir, Luma (Iraqi Journal of Science, 2025)
The study of Mars's ionosphere was made by investigating the measurements of the electron density (Ne) depending of the variation of the solar activities through different local time, different seasons, and different altitudes. The datasets has been taken from MARSIS on board the Mars Express spacecraft, the investigation for the solar indices and the electron density (Ne) have been made for two period of time depending on the strength of the geomagnetic storms, the first one was taken when the geomagnetic storms was low as in years (1998 & 2005), the data was chosen for three seasons of these years, Winter (December), Summer (June) and Spring (April). The second period was taken for the years (2001 & 2002) when the geomagnetic storms was high and the data also was chosen for three seasons as well except for Spring (March). The result of the analytical study that have been made for the electron density profile shows fluctuations that are inversely proportional with the solar flux and the sunspot number .This is attributed to the lack of the magnetic field that existed on Planet Mars.